Semantic Changes of Selected Idioms of Islamic Civilization in Nigeria : Semantics - Zakariyah, Abdulbaqy Yahya; Rufai, Aminullahi Ahmad (Al-Ḍād Journal, 2024)
Abstract: The focus of the linguists on the theory of semantic migration still remains constant. They discuss periodically on the relationship between indicative and the content, this is simply because the conception attached thereof by people has no limitation, while the indicative, word to describe the concept of meaning is limited in any language. This gives room to a word to migrate and develop semantically from one season to another. Sometimes word is described semantically as promoted and some other times as demoted. It is noted that the theory of conflict civilizations between human races has affected the Islamic civilization across the globe including Nigerian Muslims. This has posed a great threat on many terminologies known in the golden era of Islamic Civilization. The words that promote scholarship and intellectualism later turn to be demoted words that people are afraid to be associated with, i.e Al.Imam, Al-Jihad, almasjid, mimbar, Katateeb, Mallam, e.t.c. This paper is set to study the semantic development of some of these terminologies in the history of Islamic civilization in Nigeria; the paper is discussed in the following parts: Introduction, Semantic study of selected Islamic terminologies, Study of semantic development in the selected words, Influence of the theory of conflict civilization on the semantic demotion of the words, and Conclusion. Keywords: Semantic, Terminologies, Islamic, Civilization, Selected, Conflict